Youth Functioning and Experiences in Inner-City After-School Programs Among Age, Gender, and Race Groups - Roffman, Jennifer G. (2001)
Many dangers and challenges face inner-city minority children during their after-school hours. Youth development programs provide an alternative to spending this time unsupervised. We examined the relationship between children’s experiences in selected urban Boys and Girls Clubs and child functioning. Because the sample (N = 296) consisted of African American and Hispanic boys and girls, aged 10–18, we were able to compare these relationships across race, gender, and age groups. There was no relationship between simple participation levels and child functioning, but significant linkages were identified between specific elements of the club experience and functioning. Relationships with club staff members and participation in club activities were associated with better functioning for older boys, a subgroup that is at considerable risk for delinquency. In addition, enjoyment of the club and not feeling badly treated there were associated with better functioning for all groups of children.